베스트셀러 순위가 공공도서관 대출에 미치는 영향 분석: 패널자료 분석을 중심으로 - 이종욱; 강우진; 박중규; Lee, Jongwook; Kang, Woojin; Park, Jungkyu (Chŏngbo Kwalli Hakhoechi, 2021)
The purpose of this study is to analyze the effects of the bestseller ranks on the book circulations in public libraries. To achieve this goal, the weekly data sets of 179 books' library circulation and bestseller list from January 1, 2018 to December 29, 2019 were constructed based on the data collected from BigData MarketC and YES24. Three methods for analyzing panel data including linear regression, fixed-effect, and random effect models were compared, and it turned out that fixed-effect model was better than other methods. The results show that the average ranks of bestsellers were associated with their public library circulations visually. Also, the analysis of fixed-effect model showed that the single rank decline of a book on the bestseller list decreases its average circulation of 0.108 while the size of effect varied depending on subject of books. The study empirically demonstrated the impact of a bestseller list on people's book circulation behavior, suggesting that public libraries need to reference sociocultural context as well as bestseller book lists to predict library user needs and to formulate collection development policy. 본 연구에서는 베스트셀러 목록에 포함된 도서의 순위가 공공도서관에서의 평균 대출 건수에 미치는 영향을 패널분석을 통해 살펴보고자 하였다. 본 연구를 위해 문화 빅데이터 플랫폼을 통하여 국립중앙도서관이 제공하는 데이터를 바탕으로 2018년 1월 1일부터 2019년 12월 29일까지 총 104주 동안의 분석 대상 도서 179권의 공공도서관 대출 데이터 세트를 생성하였고, YES24 웹사이트를 통해 같은 기간 주간 베스트셀러 목록 데이터 세트를 구축하였다. 공공도서관 대출과 베스트셀러 도서 순위 간 정확한 관계를 확인하기 위해 패널자료의 특성을 활용한 분석 방식인 선형회귀모형, 고정효과모형, 확률효과모형 등 세 개의 모형을 비교한 결과, 고정효과모형이 가장 적합한 것으로 나타났다. 순위 데이터 결측값이 47주 미만인 179권의 도서의 자료를 고정효과모형으로 분석한 결과, 도서의 베스트셀러 순위가 한 단계 내려가면 공공도서관에서의 해당 도서 평균 대출 건수가 0.108권 유의미한 수준에서 감소한다는 것을 밝혀내었다. 또한, 베스트셀러 순위가 도서 평균 대출 건수에 미치는 효과가 도서의 내용분류에 따라 상이함을 알 수 있었다. 이 연구는 베스트셀러 순위가 사람들의 도서관 대출행태에 영향을 미치고 있음을 실증적으로 확인한 것으로, 공공도서관에서는 이용자의 요구를 예측하고, 장서 개발 정책 수립에 베스트셀러 목록을 비롯한 사회문화적 맥락을 고려할 필요가 있음을 시사한다.